2019
DOI: 10.1017/s0033291719001909
|View full text |Cite
|
Sign up to set email alerts
|

Maternal depression and inflammation during pregnancy

Abstract: BackgroundMaternal depression during pregnancy increases the risk for adverse developmental outcomes in children. However, the underpinning biological mechanisms remain unknown. We tested whether depression was associated with levels of and change in the inflammatory state during pregnancy, if early pregnancy overweight/obesity or diabetes/hypertensive pregnancy disorders accounted for/mediated these effects, and if depression added to the inflammation that typically accompanies these conditions.MethodsWe anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 64 publications
3
38
0
Order By: Relevance
“…It represents a composite signal of changes in multiple circulating glycoproteins and is suggestive of a prolonged low-grade inflammatory state (39). Both hsCRP and glycoprotein have been linked with overweight/obesity, chronic hypertension, preeclampsia, gestational diabetes and depression during pregnancy (44).…”
Section: Introductionmentioning
confidence: 99%
“…It represents a composite signal of changes in multiple circulating glycoproteins and is suggestive of a prolonged low-grade inflammatory state (39). Both hsCRP and glycoprotein have been linked with overweight/obesity, chronic hypertension, preeclampsia, gestational diabetes and depression during pregnancy (44).…”
Section: Introductionmentioning
confidence: 99%
“…Namely, in our study sample, higher hsCRP and glycoprotein acetyl levels were not only associated with early pregnancy overweight and obesity and depression, but also with preeclampsia, chronic hypertension and gestational diabetes in current pregnancy. These results have been described in the Results section of the article text and in the Supplementary Table S4 of our article (Lahti-Pulkkinen et al, 2019). Furthermore, previously unpublished analyses in our study sample showed that maternal higher mean hsCRP and glycoprotein levels across pregnancy were associated also with significantly higher maximum levels of systolic [Pearson r(355) = 0.26, p < 0.001; for hsCRP and r(327) = 0.14, p = 0.01 for glycoprotein] and diastolic [r(355) = 0.31, p < 0.001 and r(327) = 0.20, for hsCRP and glycoprotein acetyls, respectively] blood pressure during pregnancy.…”
mentioning
confidence: 65%
“…First, we thank Fujitake and Chen (2019) for their interest in our research and the letter to the editor on our recent article Maternal Depression and Inflammation during Pregnancy published in Psychological Medicine , where we showed in the Prediction and Prevention of Pre-eclampsia and Intrauterine Growth Restriction (PREDO) – pregnancy cohort, that diagnosis of depression before pregnancy and depressive symptoms during pregnancy was associated with higher levels of inflammatory biomarkers hsCRP and glycoprotein acetyls across pregnancy among 379 women (Lahti-Pulkkinen et al, 2019).…”
mentioning
confidence: 99%
“…The biological mechanisms underlying the possible effects of maternal prenatal mental health on offspring neurocognitive development may include genetic and epigenetic changes in the structure and functioning of the placenta, in the activity of the glucocorticoid regulation of the hypothalamusepituitaryeadrenal axis regulating the stress response, and in the functioning of the inflammatory system. Studies in PREDO showed that maternal depression and/or anxiety during pregnancy were associated with increased levels of proinflammatory biomarkers high-sensitive C-reactive protein and glycoprotein throughout pregnancy [35], with morphological changes in the placenta [36], with changes in placental mRNA expression of genes regulating glucocorticoid functioning [37], and with lower epigenetic gestational age [38] and altered polyepigenetic scores of glucocorticoid-responsive genes [39] of the newborn. The increased maternal proinflammatory biomarker levels during pregnancy also predicted increased neurodevelopmental delay risk in the offspring and mediated the effects of prenatal adversity on child neurodevelopmental delay [40].…”
Section: Discussionmentioning
confidence: 99%